Evaluation of antibodies against hydatid cyst fluid antigens in the post-treatment follow-up of cystic echinococcosis patients - Celik, Tuncay; Akarsu, Guelay Aral; Gungor, Cigdem; Colak, Cemil; Ormeci, Necati (Int Scientific Information, Inc, 2009)
Background: Cystic echinococcosis (CE), caused by the metacestode stage of Echinococcus granulosus, is one of the most important zoonoses worldwide. Long post-treatment follow-up is required because of possible relapse. The objective of this study was to determine the values of different antigenic fractions of sheep hydatid cyst fluid in the follow-up of CE patients after treatment. Material/Methods: After gradient gel electrophoresis of sheep hydatid cyst fluid, 45 post-treatment (1 month - 16 years) serum samples of CE patients treated with PAIR (puncture, aspirations, injection, and respiration) and five post-treatment (1 month) sera of operated CE patients were studied using Western blot. Twenty healthy individuals and five patients infected with other helminths served as controls. Results: Antigens with molecular weights of 6.5-8, 14, 20, 29, 45, 50, 66, 116-120, 205, and 215 kDa were identified. The bands detected at the highest frequency were 29 kDa (10.4%), 45 kDa (17.2%), and 66 kDa (12.8%). Sera of the 20 healthy controls recognized no specific bands. All of the sera of the five patients with other parasitic diseases recognized one or more hydatid cyst fluid antigens. There was a statistically significant difference between the time after treatment and band weights (p<0.0001). Conclusions: The protein bands of 29 and 205-215 kDa may be valuable in the follow-up of cystic echinococcosis patients as they disappear one year and six months, respectively, after therapy.
Keywords: cystic echinococcosis; antigen; treatment follow-up